THE EFFECT OF RENTAL PRICES OF PREMISES, LOCATIONS AND FACILITIES ON THE INCOME OF TRADERS IN THE UPHEAVAL OF MARINE FISH IN THE CENTER OF MEDAN MARKET - cynthia tanuwijaya (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine the effect of Rental Prices for Places, Locations and Facilities on the income of fish traders in the Market Center. The research method used is quantitative research with a survey method that uses questionnaires as a research instrument to collect data. The population in this study was marine fish traders in the Market Center with a population of 68 people. Multiple linear regression research tests are used as an analytical tool to find out how the influence between independent and dependent variables is. The results of this study show that both partially and simultaneously the variable Rental Price of Premises, Locations, Facilities has a significant effect on the Income of Fish Traders in the Market Center. The variable Rental Price of Premises, Locations, Facilities is able to explain the variations that occur in the Income of Fish Traders by 44.4%. This is due to the influence between the Rental Price of The Place, Location, and Facilities on Merchant Income.